Subfoveal Choroidal Thickness after Panretinal Photocoagulation with Red and Green Laser in Bilateral Proliferative Diabetic Retinopathy Patients: Short Term Results - Ramak Roohipoor; Sina Dantism; Aliasghar Ahmadraji; Reza Karkhaneh; Mohammad Zarei; Fariba Ghasemi (Journal of Ophthalmology)
Purpose. To compare subfoveal choroidal, central retinal, and peripapillary nerve fiber layer (RNFL) thickness after panretinal photocoagulation (PRP) with red and green laser in diabetic patients. Study Design. Randomized clinical trial. Methods. A total of 50 patients with bilateral proliferative diabetic retinopathy and no diabetic macular edema underwent PRP. One eye was randomly assigned to red or green laser. Subfoveal choroidal, central retinal, and RNFL thicknesses were evaluated at baseline and 6 weeks after treatment. Results. The mean subfoveal choroidal, central retinal, and peripapillary nerve fiber layer (RNFL) thickness increased significantly in each eye 6 weeks after PRP (P values in red laser group: <0.01, 0.03, and <0.01, resp., and in green laser group <0.01, <0.01, and <0.01). There was no difference between red and green laser considering subfoveal choroidal, central retinal, and peripapillary nerve fiber layer (RNFL) thickness increase after PRP (P values: 0.184, 0.404, and 0.726, resp.). Conclusion. Both red and green lasers increased mean subfoveal choroidal, central retinal, and peripapillary nerve fiber layer (RNFL) thickness significantly 6 weeks after PRP, but there is no difference between these two modalities in this regard.